Ethical AI surveillance in the workplace - Kritikos, Mihalis (Emerald Publishing Limited, 2023)
With surveillance at work extending into the home and the deployment of AI in the workplace already rapidly expanding, concerns have been raised about the ramifications of these developments. Blurring the boundaries between public and private spheres, digital workplace monitoring and digital activity tracking seem set to raise stress levels and undermine trust between employers and employees as they threaten to further infiltrate the world of work. Proposing a clear list of policy options, Ethical AI Surveillance in the Workplace tackles the structural challenges associated with 'wiring the labour market', including issues of control, autonomy and voice. From Data Protection Impact Assessments to regulatory sandboxes, and from establishing the right to disconnect to setting up a Code of Ethical Workplace Monitoring, the proposed paths aim to safeguard a responsible deployment of AI-powered monitoring tools within the workplace and protect employees as data subjects whose digital footprints are under constant scrutiny. Wielding the legal, regulatory and institutional tools available, this uniquely structured analysis acts as a comprehensive starting point for discussing these ever-evolving challenges and how they may shape the future of the workplace.
Includes index.
Keywords: Work environment -- Technological innovations.; Artificial intelligence.; Office & workplace.; elektronické knihy; electronic books